Public resource management reform programs - Attinasi, Maria Grazia (Asian Development Bank, 2008)
Public resource management reform programs constitute an important are of support by the Asian Development Bank for developing member countries, particularly in South Asia. These programs seck to create fiscal space through structural reform by combining policy reform measures across a broad range of activities, including fiscal programming, management and control of expenditures, and revenue management of fiscal front.